Monte Carlo Simulation of an X-Ray Pixel Beam Microirradiation System - Schreiber, E. C. (Radiat Res, 2009)
Monte Carlo simulations are used in the development of a nanotechnology-based multi-pixel beam array small animal microirradiation system. The microirradiation system uses carbon nanotube field emission technology to generate arrays of individually controllable X-ray pixel beams that electronically form irregular irradiation fields having intensity and temporal modulation without any mechanical motion. The microirradiation system, once developed, will be incorporated with the micro-CT system already developed that is based on the same nanotechnology to form an integrated image-guided and intensity-modulated microirradiation system for high-temporal-resolution small animal research. Prospective microirradiation designs were evaluated based on dosimetry calculated using EGSnrc-based Monte Carlo simulations. Design aspects studied included X-ray anode design, collimator design, and dosimetric considerations such as beam energy, dose rate, inhomogeneity correction, and the microirradiation treatment planning strategies. The dosimetric properties of beam energies between 80–400 kVp with varying filtration were studied, producing a pixel beam dose rate per current of 0.35–13 Gy per min per mA at the microirradiation isocenter. Using opposing multi-pixel-beam array pairs reduces the dose inhomogeneity between adjacent pixel beams to negligible levels near the isocenter and 20% near the mouse surface.